Immature platelets in patients with Covid-19: association with disease severity. (14th October 2021) - Harari, E; Cohen, A; Cipok, M; Bryk, G; Karp Lador, N; Mann, T; Mayo, A; Lev, E I
Abstract: Background: Coronavirus disease 2019 (Covid-19) is associated with a high incidence of thromboembolic events, both venous and arterial. Currently, there are no clinical or laboratory markers to guide risk-stratification or antithrombotic therapy in Covid-19 patients. Circulating immature platelets represent a population of hyper-reactive platelets, which are associated with arterial thrombotic events. Objectives: To assess whether the proportion of immature platelets in the circulation is associated with disease severity in patients with Covid-19 Methods: This prospective study evaluated consecutive patients with COVID-19 admitted with various degrees of disease severity, as determined by the standard Covid-19 severity Score. Disease severity was evaluated during hospitalization. Immature platelet fraction (IPF) absolute number and percentage were measured on admission and at additional time points during the hospital course using the SysmexXN-3000 auto-analyzer. The maximal values of IPF% and absolute IPF was analyzed according to disease severity. Results: A total of 136 consecutive patients with Covid-19 were recruited. Mean age was 60±19 years for patients with mild and moderate disease and 69±14 years for patients with severe disease, 52% with mild and moderate disease and 48% with severe disease were woman, 11% with mild and moderate disease and 20% with severe disease with concurrent cardiovascular disease The median of IPF% was higher in the severe COVID-19 group compared to patients with mild or moderate disease [4.2 (IQR 2.73–6.45) vs 5.8 (IQR 3.9–8.7), P=0.01, Figure 1)]. The median of IPF absolute number was also significantly higher in patients with severe disease comparing to patients with mild or moderate disease (4.2 (2.85–6.1) vs 5.1 (IQR 3.65–7.35), P<0.0001, Figure 2]. Conclusions: Patients with severe Covid-19 have a higher level of IPF in the circulation than patients with mild or moderate disease. IPF may serve as a reliable prognostic marker for in-hospital disease severity in patients with Covid-19 FUNDunding Acknowledgement: Type of funding sources: None.